2021
DOI: 10.1186/s13037-021-00296-4
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: The safety of Covid-19 mRNA vaccines: a review

Abstract: Following publication of the original article [1], it was noticed that the published version of this article has contained incorrect title. The correct title is "The safety of Covid-19 mRNA vaccines: a review". The original article has been corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…We here assumed that the parameters 𝐻𝐻 1 , 𝐻𝐻 2 , 𝜂𝜂 1 , 𝜂𝜂 2 , and 𝑚𝑚 varied across individuals, whereas we did not consider interindividual variability in other parameters to ensure parameter identifiability. Note that the half-life of mRNA (i.e., log 2 /𝑑𝑑) and dose of mRNA (i.e., 𝐷𝐷 𝑖𝑖 ) are assumed to be 1 day 45 and 100 (𝜇𝜇𝜇𝜇/0.5mL) 46 , respectively. Fixed effect and random effect were estimated by using the stochastic approximation expectation-approximation algorithm and empirical Bayes' method, respectively.…”
Section: Quantifying Vaccine-elicited Time-course Antibody Dynamicsmentioning
confidence: 99%
“…We here assumed that the parameters 𝐻𝐻 1 , 𝐻𝐻 2 , 𝜂𝜂 1 , 𝜂𝜂 2 , and 𝑚𝑚 varied across individuals, whereas we did not consider interindividual variability in other parameters to ensure parameter identifiability. Note that the half-life of mRNA (i.e., log 2 /𝑑𝑑) and dose of mRNA (i.e., 𝐷𝐷 𝑖𝑖 ) are assumed to be 1 day 45 and 100 (𝜇𝜇𝜇𝜇/0.5mL) 46 , respectively. Fixed effect and random effect were estimated by using the stochastic approximation expectation-approximation algorithm and empirical Bayes' method, respectively.…”
Section: Quantifying Vaccine-elicited Time-course Antibody Dynamicsmentioning
confidence: 99%
“…As for (PCV), the highest percentage of it was in the people vaccinated with AstraZeneca and Sinofam (43.8 and (43.0) respectively, and the highest percentage of (PLT) for those vaccinated with Pfizer and Sinopharma (269.0 and 270.6), respectively, and by comparing the results to the control group between the vaccinated and the unvaccinated, as well as between the type of vaccine, there were no significant statistical and moral differences and effects at the level of significance (P ≤0.05. ( Where studies have shown that the Pfizer vaccine is safe and effective for the majority of the population, it provides a high level of protection, as it can be licensed for emergency use (Anand & Stahel, 2021)…”
Section: Comparison Of Blood Counts With Vaccinated and Unvaccinated ...mentioning
confidence: 99%
“…By comparing the results with the control group between the vaccinated and the unvaccinated, as well as between the type of vaccine, there were no significant statistical and moral differences and effects at the level of significance (P < 0.05.) Where studies have shown that the Pfizer vaccine is safe and effective for the majority of the population, as it provides a high level of protection against the disease and can be licensed for emergency use (Anand & Stahel, 2021), while another study indicated the effectiveness of the Oxford-AstraZeneca (ChAdOx1 nCoV-19 vaccine) as its value The European Medicines Agency (EMA) Pharmacovigilance Risk Assessment Committee on March 18, 2021 declared that it is a safe and effective vaccine that contributes to the control of the COVID-19 pandemic and that the benefits of a vaccine outweigh the risks that can contribute to the control of the COVID-19 pandemic.…”
Section: Comparison Of Liver Function With Vaccinated and Unvaccinate...mentioning
confidence: 99%